Comparative epidemiology and quantitative neuroimaging of neuromyelitis optica spectrum disorder and multiple sclerosis - Chou, I-Jun (2017)
Background: Central Nervous System (CNS) inflammatory syndromes represent a spectrum of diseases caused by infiltration of inflammatory cells into the tissue of the brain and spinal cord. They comprise a group of diseases that can be acute or chronic, including optic neuritis, transverse myelitis, acute disseminated encephalomyelitis (ADEM), neuromyelitis optica (NMO) and its spectrum disorders (NMOSD), clinically isolated syndrome (CIS) and multiple sclerosis (MS). MS is the most common one while NMO/NMOSD is relatively rare although the exact population-based epidemiological parameters are lacking. The distinction of MS and NMO/NMOSD in adult patients and of MS and ADEM in paediatric patients is important for considerations of prognosis and treatment. This thesis aims to differentiate NMO/NMOSD from MS using epidemiology analyses and quantitative magnetic resonance imaging at 7 Tesla. The hypothesis of the thesis is that NMO/NMOSD can be differentiated from MS by disease incidence, prevalence, severity, and the quantitative characteristics of the lesion and non-lesion white matter of the brain.